2016
DOI: 10.3354/ab00664
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell PCR of the luciferase conserved catalytic domain reveals a unique cluster in the toxic bioluminescent dinoflagellate Pyrodinium bahamense

Abstract: Pyrodinium bahamense is a toxic, bioluminescent dinoflagellate with a record of intense bloom formation in both the Atlantic-Caribbean and Indo-Pacific regions. To date, limited genetic information exists for P. bahamense in comparison to other closely related harmful algal bloom taxa such as Alexandrium, or other bioluminescent taxa such as Pyrocystis. This study utilized single-cell PCR to explore the molecular diversity of P. bahamense within the Indian River Lagoon (IRL), Florida, USA, and a bioluminescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
6
0
5
Order By: Relevance
“…Large subunit rRNA gene sequence analysis indicated the existence of Indo-Pacific and Atlantic-Caribbean ribotypes, leading to the suggestions that P. bahamense is a species complex. A previous study showed 18S rRNA gene sequences of P. bahamense from multiple locations in the IRL, Puerto Rico, and the Indo- Pacific to be nearly identical and forming a single cluster [ 48 ]. Comparison of 18S rRNA gene sequences from sxtA4+ and sxtA4- genotype cells in this study were compared to existing 18S rRNA gene sequences from the Indo-Pacific and Atlantic-Caribbean.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large subunit rRNA gene sequence analysis indicated the existence of Indo-Pacific and Atlantic-Caribbean ribotypes, leading to the suggestions that P. bahamense is a species complex. A previous study showed 18S rRNA gene sequences of P. bahamense from multiple locations in the IRL, Puerto Rico, and the Indo- Pacific to be nearly identical and forming a single cluster [ 48 ]. Comparison of 18S rRNA gene sequences from sxtA4+ and sxtA4- genotype cells in this study were compared to existing 18S rRNA gene sequences from the Indo-Pacific and Atlantic-Caribbean.…”
Section: Discussionmentioning
confidence: 99%
“…Single cells were isolated for lysis and subsequent multiplex PCR using a slight modification of a protocol described previously [ 48 ]. Briefly, an aliquot (ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…than Alexandrium spp. suggesting a much greater variation than that seen in bioluminescent species with known gene variants (Cusick et al, 2016).…”
Section: Molecular Studiesmentioning
confidence: 95%
“…Its distribution in the Pacific coast extends from southern GOLCA to Colombia (Martínez-López et al, 2007;Rodríguez-Salvador and Meave del Castillo, 2007;Morquecho, 2008;Gárate-Lizárraga and González-Armas, 2011;Usup et al, 2012). In the Atlantic coast it has been reported from the Gulf of Mexico to Uruguay Limoges et al, 2015;Mertens et al, 2015;Poot-Delgado et al, 2015;Cusick et al, 2016). HABs have been linked in several occasions to human poisoning (Rosales-Loessener, 1989;Rodríguez et al, 1990;Saldate-Castañeda et al, 1991;Núñez-Vázquez et al, 2011;Gárate-Lizárraga et al, 2012;Callejas et al, 2015) as well as to epizootic events (fish and sea turtles) Amaya et al, 2018) ( Table 1).…”
Section: Pyrodinium Bahamensementioning
confidence: 99%